Specific Small Molecule Inhibitors of Skp2-Mediated p27 Degradation - Wu, Lily (2012)
In the ubiquitin proteasome system, the E3 ligase SCF-Skp2 and its accessory protein Cks1 promote proliferation largely by inducing the degradation of the CDK inhibitor p27. Overexpression of Skp2 in human cancers correlates with poor prognosis, and deregulation of SCF-Skp2-Cks1 promotes tumorigenesis in animal models. We identified small molecule inhibitors specific to SCF-Skp2 activity using in silico screens targeted to the binding interface for p27. These compounds selectively inhibited Skp2-mediated p27 degradation by reducing p27 binding through key compound-receptor contacts. In cancer cells, the compounds induced p27 accumulation in a Skp2-dependent manner and promoted cell-type specific blocks in the G1 or G2/M phases. Designing SCF-Skp2 specific inhibitors may be a novel strategy to treat cancers dependent on the Skp2-p27 axis.